Rosa-Isabel MARTÍNEZ LILLO, Cuatro autores de la "Liga Literaria": Yubran Jalil Yubran, Mija’il Nu’ayma, Iliya Abu-Madi, Nasib ’Arida. - Abumalham, Montserrat (Anaquel de Estudios Árabes, 1995)
Sin resumen